Enhanced mechanical and corrosion behavior of ultrafine- grained aluminium alloy coated with ZrO2 using sol-gel- assisted dip coating technique - Nur Anis Nabila, Mokhtar; Zahiruddeen Salam, Zahari; Dayangku Noorfazidah, Awang Sh'ri (AIP Publishing, 2022)
For the lightweight metal group, the development of aluminium alloys 6061 with both high corrosion resistance and good mechanical properties is a long-standing requirement. It is proposed to combine different die angles of equal channel angular pressing (ECAP) and surface treatment to achieve simultaneous improvements in the anti-corrosion and mechanical efficiency of AA6061. The objectives of the current study are to improve the mechanical properties and control the long-term corrosion properties, ECAP treated sol-gel assisted dip-coating using zirconia oxide (ZrO2) thin film. The coated ECAPed AA6061 was processed at 526°C at two different die angles of 120° and 126° to obtain ultra-fine grains (UFG), followed by a thin film coating of ZrO2 annealed for 2 hours at 200°C. The coated ECAPed AA6061 were divided into two conditions of ZrO2 thin film which are three layers and seven layers coatings thin film. Experimental results showed that coated ECAPed AA6061 made the mechanical properties improved by 44.751% for ECAP 126° 3L, 63.774% for ECAP 120° 3L, 106.355% for ECAP 126° 7L, and 140.025% for ECAP 120° 7L when compared to bare aluminium alloy. The open circuit potential and the Tafel curve of potentiodynamic results indicated that the corrosion resistance of the ECAP coated sample is better than that of the ECAP uncoated and the coating ZrO2 can significantly increase the corrosion resistance of both ECAP 120° and ECAP 126°. The treated sample shows substantially improved corrosion resistance, with less density of corrosion present. The microstructural analysis discloses that coated ECAPed samples have refined grain size with smaller precipitate particulate and ZrO2 thin film successfully adhere on the surface. However, ZrO2 thin films are non-uniform layers with different average sizes of ZrO2 particles. No cracks were observed in this study. The various dislocations and grain boundaries in the UFG substrate provide an accelerated driving force for hydrothermal reaction, promoting the creation of a thicker and more compact ZrO2 coating layer. Such a protective coating layer along with the annealed substrate with fewer crystal defects effectively retards the deterioration of corrosion and consequently maintains mechanical efficiency. The enhanced heterogeneous substrate microstructure results in superior adherent properties were observed. The proposed coated ECAP processing and the resulting extensive properties should also apply to the other aluminium alloys.